Pengaruh Fasilitas Kantor, Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Guru Di SMP Negeri 5 Mataram - Ketut Dina Kristina; Syaiful Amri; Putri Reno Kemala sari (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2023)
This study aims to examine several things, namely: (1) the effect of office facilities on performance, (2) the effect of work discipline on performance, (3) the effect of work motivation on performance, (4) the influence of office facilities, work discipline and work motivation on performance. This research includes the type of associative research. The population in this study were 51 teachers at SMP Negeri 5 Mataram and a sample of 35 people was taken using a purposive sampling technique. The data collection technique used in this study was in the form of a statement in the form of a questionnaire. The results showed that: (1) Office facilities have no significant effect on performance (2) Work discipline has a significant effect on performance (3) Work motivation has no significant effect (4) Office facilities, work discipline and work motivation have a significant effect on performance.